Atomistic molecular dynamics simulations of typical and atypical antipsychotic drugs at the dopamine D2 receptor (D2R) elucidates their inhibition mechanism. Issue 4 (12th March 2017) - Salmas, Ramin Ekhteiari; Yurtsever, Mine; Durdagi, Serdar
Abstract : Dopamine D2 receptor (D2R) plays a pivotal role in nervous systems. Its dysfunction leads to the schizophrenia, Parkinson's diseases and drug addiction. Since the crystal structure of the D2R was not solved yet, discovering of potent and highly selective anti-psychotic drugs carry challenges for different neurodegenerative diseases. In the current study, we modeled the three-dimensional (3D) structure of the D2R based on a recently crystallized structure of the dopamine D3 receptor. These two receptors share a high amino acid sequence homology (>70%). The interaction of the modeled receptor with well-known atypical and typical anti-psychotic drugs and the inhibition mechanisms of drugs at the catalytic domain were studied via atomistic molecular dynamics simulations. Our results revealed that, class-I and class-II forms of atypical and typical D2R antagonists follow different pathways in the inhibition of the D2Rs.